Sensorless parameter estimation of VFD based cascade centrifugal pumping system using automatic pump curve adaption method. (November 2021) - V.K., Arun Shankar; Subramaniam, Umashankar; Madurai Elavarasan, Rajvikram; Raju, Kannadasan; Shanmugam, Paramasivam
Abstract: The Sustainable Development Goal 7 necessitates efficient energy utilization and aligning energy efficiency targets to industrial machines would pave a way for prospective developments. Pumps are inevitable in commercial and industrial sectors and they contribute to nearly 22% of the global industrial energy utilization. Attesting the fact, this paper focuses on the energy-efficient operation of a pumping system by governing the speed using Variable Frequency Drives (VFDs). This is accomplished by modeling the pump performance curves by estimating the parameters like flow rate and pressure values for automatic adaptation in VFDs. With the aid of the manufacturers' datasheet and the operating state of the pump, the pump performance curve is estimated automatically. The pump operating point is attained from pump parameters and motor rotational speed without using the sensors (sensor-less). This proposed methodology is validated through an experimental setup with a 1.1 kW Induction motor (IM) based centrifugal pump driven by 2.2 kW Danfoss VFD and the obtained results can be adopted for estimating the operating point of the centrifugal pumps throughout its operating range. Further, the variations in accuracy between actual and measured flow rate for the proposed scheme is found to be ranging from −5.29 GPM to 2.03 GPM which is about −0.243% to 0.0713%. Specifically, the pump flow rate estimation accuracy deviation is found to be between 2%–8% during lower operating flow rates and is within 2% during the higher operating region. Further, the proposed scheme offers better efficiency than the conventional sensor-based method which constitutes about 2% deviation in accuracy. Consequently, it empowers Industrial users to perform energy-efficient optimization for the cascade pumping system. Highlights: Investigates modeling of pump curves for automatic adaptation in VFDs. Presents estimation of flow rate and pressure values in pumping system. Suggests energy optimization for cascade pumping system. Reviews relation between pump parameters and motor rotational speed. Highlights identification of performance curves from the pump datasheet.